Correlation between current-assisted transversal anisotropy adjustment and magnetoimpedance enhancement in Fe-based micro-wires - D. H. Hoang; N. V. Tuan; H. A. Tam; N. K. Binh; P. M. Vuong; H. S. Hong; V. D. Lam; L. V. Lich; Do, Giang Thi Huong (Communications in Physics, 2025)
This paper focuses on the study of the magnetization dynamics and the magnetoimpedance of micro-sized magnetic conductors assisted by a DC current wire carrying. The research methodology combines experimental fabrication and finite element simulation, on that basis, the study explains and proposes the dependence of magnetic properties, magnetization process and magnetoimpedance various variables such as on the current magnitude and angular dependency between the external magnetic field and the micro-wire direction. These variables allow to optimize magnetoimpedance effect toward high resolution magnetic field applications. The obtained results have been discussed by considering the energy contribution including the Zeemann from the external magnetic field and the magnetic field generated by the current, shape anisotropy energy and thermal energy to the magnetization process and the magnetoimpedance effect.